Functions for Retinoic Acid-Related Orphan Receptor Alpha (RORα) in the Activation of Macrophages During Lipopolysaccharide-Induced Septic Shock - Hams, Emily; Roberts, Joseph; Bermingham, Rachel; Fallon, Padraic G. (Frontiers in Immunology, 2021)
The transcription factor ROR plays an important role in regulating circadian rhythm, inflammation, metabolism and cellular development. Herein we show that in the absence of functional ROR in mice there is reduced susceptibility to LPS-induced endotoxic shock, with selective decreases in release of pro-inflammatory cytokines. Treatment of mice with a ROR selective synthetic inhibitor also reduced the severity of LPS-induced endotoxemia. The reduction in responses in Rora deficient mice was associated with an alterations in metabolic and pro-inflammatory functions of macrophages, both in vivo peritoneal macrophages and in vitro generated bone marrow derived macrophages. Using LysMCreRorafl/sg mice the reduced susceptibility to LPS was shown to be specific to Rora expression in the macrophages. This study identifies that Rora-mediated regulation of macrophages impacts on the pro-inflammatory responses elicited by LPS.